Variants of storage and perioperative use of autologous blood components - Yu. S. Bocharova; V. A. Sorokovikov; S. N. Bocharov (Acta Biomedica Scientifica, 2013)
The article is devoted to the problem of perioperative blood replacement in selective surgery by the way that is based on the principle of normalization of transcapillary exchange with use of different variants of autologous blood components storage. Main method of blood replacements is hypervolemic hemodilution with use of crystalloid and colloid solutions. But in conditions of acute massive blood loss this method allows to provide maintenance of effective hemodynamics for a short period of time only. This method is used without taking effectiveness of transcapillary exchange of a patient into account and. its main feature is 3 times exceeding of infusion medium volume over blood loss volume. These case is accompanied by the transfer of liquid from bloodstream to interstitial space and. hypostasis of the latter, that shows itself in functional disorder of target organs and. in formation of syndrome of polyorganic insufficiency: respiratory syndrome, hepatargia, disorder of transitory function of gastrointestinal tract etc. Thereupon the most preferable and. righteous is the method of blood replacement that is based on the principle of normalization of transcapillary exchange taking volemic coefficients of transfused solutions into account. Advantages and. features of this method include decrease of volume of infusion medium to the level equal to the blood loss volume; absence of hypostasis of interstitial space; exclusion of possibility of development of polyorganic insufficiency syndrome. Techniques of storage of autologous blood components were used to increase effectiveness of this method and. to minimize using of donated blood components. As the result of the research we determined that the most effective is single storage of autologous blood in volume of 10 % of circulation blood volume 3 days before the operation. This blood has anti-ischemic action, stimulate erythropoiesis, resolve functional state of hemostasis system. Another one effective technique of this method is return of drainage secretion that is almost similar to the venous blood of patient by its composition, except for thrombocytes. Return of drainage blood is safe for the patient and isn't accompanied by any reactions or organs injuries. High clinical effectiveness of this method of blood replacement is proved by the possibilities of patient to keep effective stontaneous breathing without artificial pulmonary ventilation even at blood loss volume of 90 % of circulation blood volume.